Improving management of enterprises based on corporate governance (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2024)
In the era of rapid economic development, corporate governance plays an increasingly important role in the development of enterprises. High-quality accounting information has a profound impact on the company’s internal environment. Corporate governance is the owner’s rectification and improvement of the internal organization of the enterprise, and formulates a solution to its own problems. The improvement of corporate governance requires the specification of accounting information.